2007
DOI: 10.1152/ajpregu.00423.2007
|View full text |Cite
|
Sign up to set email alerts
|

Temporal extracellular matrix adaptations in ligament during wound healing and hindlimb unloading

Abstract: Martinez DA, Vailas AC, Vanderby R Jr, Grindeland RE. Temporal extracellular matrix adaptations in ligament during wound healing and hindlimb unloading. Am J Physiol Regul Integr Comp Physiol 293: R1552-R1560, 2007. First published August 15, 2007 doi:10.1152/ajpregu.00423.2007.-Previous data from spaceflight studies indicate that injured muscle and bone heal slowly and abnormally compared with ground controls, strongly suggesting that ligaments or tendons may not repair optimally as well. Thus the objective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
37
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 39 publications
3
37
1
Order By: Relevance
“…The MCL injury models have shown a similar increase in Col I and III expression for up to 12 weeks postoperatively. 29,33 A study using rat tendon fascicles found that application of cyclic strain over a 24-hour period increased the production and retention of newly synthesized collagen fascicles in comparison with shorter durations, which inhibited collagen synthesis. 31 Vol.…”
Section: Discussionmentioning
confidence: 99%
“…The MCL injury models have shown a similar increase in Col I and III expression for up to 12 weeks postoperatively. 29,33 A study using rat tendon fascicles found that application of cyclic strain over a 24-hour period increased the production and retention of newly synthesized collagen fascicles in comparison with shorter durations, which inhibited collagen synthesis. 31 Vol.…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence from animal models that mechanically loading injured soft tissue prompts a range of cellular responses that promote tissue structural change and recovery 11. These responses include an upregulation of mRNA expression for key proteins associated with soft tissue healing,1214 and enhanced strength and morphological characteristics of collagenous tissue 12 13…”
Section: Introductionmentioning
confidence: 99%
“…Research performed on rats revealed bone healing impairment, with reduced callus formation and reduced angiogenesis (Midura et al 2006), disruptions in the microvasculature of injured muscles, with delayed muscle repair processes (Heinemeier et al 2009), reduced ECM deposition in tendons and ligaments, with corresponding decrease in strength and alteration of repair mechanisms in connective tissues (Provenzano et al 2003;Martinez et al 2007). Moreover, impaired angiogenesis has been reported (Radek et al 2008).…”
Section: Introductionmentioning
confidence: 99%